INTERVENSI ERGONOMI PADA AKTIVITAS BELAJAR DI RUMAH KOS DAERAH DINGIN MENINGKATKAN KINERJA MAHASISWA - Pungus, Meity Martina; Tirtayasa, Ketut (Bumi Lestari; Vol 11 No 1 (2011), 2011)
Learning activity at home is a routine task performed by the students as the implementation of academic curriculum. Most of activities done by the students in respect to the implementation of the academic curriculum such as in preparing self and structured tasks, in writing practicum reports, in preparing for the mid and last exams of the semester, are done at home. In general, the students of the faculty of mathematics and natural sciences (FMNS), Manado State University, live in homes of Minahasa tradition. In fact, conventional activity done by the students at the lease home of Minahasa tradition in cool area showed unfavorable risks to students based on the load of learning with indicators of musculoskeletal complaints, boredom, and fatigue. Consequently, the students were not yet able to attain the intended performance based on indicators the accuracy, speed, constancy and the results of working. In other words, the conventional activity is not able to be an ergonomic one. To overcome the problems, by using total ergonomics approach (TEA), it has made the efforts of ergonomics interventions. In order to test the capability of the ergonomics interventions, it had been done a research with the hypothesis, the ergonomics interventions on the activity in boardinghouse of Minahasa tradition: (1) increases the accuracy of working; (2) increase the speed of working; (3) increase the constancy of working; and (4) increase the results of working of the students. This research was done in two periods by utilizing the treatment by subject design. The first period, without intervention, was done during four weeks. The second period, with intervention, was also done during four weeks. The subjects utilized in the research were as many as 15 persons. The measurements of dependent variables were done before and after doing the activity of learning in every unit of activity. The results of the research showed that the ergonomics interventions on the learning activities in boardinghouse could significantly (p<0.05): (1) increases the accuracy of working 55.06%; (2) increase the speed of working 17.32%; (3) increase the constancy of working 30.72%; and (4) increase the results of working of the students 131.44%. The ergonomics interventions were successful in overcoming the ergonomic problems in the learning activity in boardinghouse. Based on the research it can be concluded that the ergonomics interventions can increase the performance of the students with indicators; increasing the accuracy of working; increasing the speed of working; increasing the constancy of working; and increasing the results of working of the students. It can be suggested that for the lecture of Basics Physics II, the learning activity with ergonomic interventions can be an alternative for the lecturer team so that the students achieve the intended performance.
Keywords: ergonomic intervention; boardinghouse of Minahasa tradition; work of learning; performance; student